2022
DOI: 10.3390/su14127150
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Customer Behavior of Using Contactless Payment in China: A Comparative Study of Facial Recognition Payment and Mobile QR-Code Payment

Abstract: Emerging technologies have made tremendous changes in people’s daily lives, and they have profoundly influenced their economic and consumption activities. Recently, the COVID-19 pandemic has also drastically increased individuals’ usage of contactless payment technologies, such as mobile and facial recognition payments, which has accelerated the transformation of digital transaction services in China. In this study, the findings show that perceived usefulness, perceived ease of use, and service security can af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…However, the results on the impact of perceived ease of use on intention have been inconsistent. Zhong and Moon (2022), Ibrahim et al 2019;Senali et al (2022), Sukwadi et al (2022), andTang et al (2022) found a significant positive relationship between perceived ease of use and consumers' intention to use QR code. This is also consistent with empirical research from numerous studies (Hewawasam et al, 2022;Susanti & Alamsyah, 2022).…”
Section: Perceived Usefulnessmentioning
confidence: 90%
“…However, the results on the impact of perceived ease of use on intention have been inconsistent. Zhong and Moon (2022), Ibrahim et al 2019;Senali et al (2022), Sukwadi et al (2022), andTang et al (2022) found a significant positive relationship between perceived ease of use and consumers' intention to use QR code. This is also consistent with empirical research from numerous studies (Hewawasam et al, 2022;Susanti & Alamsyah, 2022).…”
Section: Perceived Usefulnessmentioning
confidence: 90%
“…In addition to the future research directions mentioned in accepted by them. Second, the FRPS in China is becoming a popular contactless payment system due to its convenience (Zhong & Moon, 2022).…”
Section: Emerging Research Areas In Mpsmentioning
confidence: 99%
“…Researchers may investigate the reason for the lower acceptance of BNPL by the older generation and what factors BNPL providers need to consider to make it accepted by them. Second, the FRPS in China is becoming a popular contactless payment system due to its convenience (Zhong & Moon, 2022). If the FRPS is adopted, it may pose competition to MPS, considering its advantages over MPS.…”
Section: Future Research Agendamentioning
confidence: 99%
“…Inadequate system quality increases difficulties in using the application and prevents users from enjoying or being happy with the product (Saadillah et al 2021 ). Studies designed related to QR code use indicate that system quality, including ease of use and usability, positively affects customer satisfaction following the experience (Zhong and Moon 2022 ). Problems in system quality for digital payment negatively affect customer experience (Zhou 2013 ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%